Ischemic and Bleeding Events of Ticagrelor Monotherapy in Korean Patients With and Without Diabetes Mellitus: Insights From the TICO Trial - Yun, Kyeong Ho; Cho, Jae Young; Lee, Seung Yul; Rhee, Sang Jae; Kim, Byeong Keuk; Hong, Myeong Ki; Jang, Yangsoo; Oh, Seok Kyu; , the TICO Investigators (Frontiers in Pharmacology, 2021)
Background: Ticagrelor monotherapy after 3-month dual antiplatelet therapy (DAPT) with aspirin and ticagrelor can reduce bleeding without increasing ischemic events after percutaneous coronary intervention (PCI). However, the impact of this approach among the patient with diabetes remains unknown. Methods: This was a sub-analysis of the Ticagrelor Monotherapy after 3 Months in the Patients Treated with New Generation Sirolimus Eluting Stent for Acute Coronary Syndrome (TICO) trial. After successful PCI, the patients were randomly assigned to ticagrelor monotherapy after 3-month DPAT or to ticagrelor-based 12-month DAPT. We compared ischemic events and bleeding events between the patients with diabetes and without diabetes for 12 months. Ischemic events were defined as death, myocardial infarction, ischemic stroke, transient ischemic attack, stent thrombosis, and any revascularizations. Bleeding events were defined according to the Thrombolysis in Myocardial Infarction (TIMI) criteria and Bleeding Academic Research Consortium (BARC) definition. Results: Between August 2015 and October 2018, 3056 patients were enrolled in the TICO trial, of which 835 (27.3%) had diabetes mellitus. Diabetes mellitus was associated with all evaluated ischemic and bleeding events. No significant differences in any ischemic events were observed in patients with diabetes between ticagrelor monotherapy after 3-month DAPT and ticagrelor-based 12-month DAPT (hazard ratio [HR] 0.83, 95% confidence interval [CI] 0.45-1.52, p=0.540). In patients with diabetes, the overall incidence of bleeding complications during the 12-month follow-up period did not differ between the two treatment groups (HR 0.83, 95% CI 1.48-1.43, p = 0.505). However, ticagrelor monotherapy was significantly reduced both any TIMI bleeding and BARC 3 or 5 bleeding events in diabetes patients in the 3-month landmark analysis, after 3-month DAPT period (HR 0.20, 95% CI 0.07-0.59, p = 0.003). Conclusions: In diabetic patients, ticagrelor monotherapy showed a lower incidence of bleeding complications after 3-month DAPT period, without increasing ischemic complications, compared with ticagrelor-based 12-month DAPT.